Diversity and habitat preference of orchirds in R. Soerjo Forest Park, East Java, Indonesia - Rohmah, Laila Ainur; Elyasa, Ayu Tya; Nugraheni, Tunjung; Pratama, Bella Pratiwi Kurnia; Sakna, Bariznaba’us (Generasi Biologi Indonesia, 2023)
The diversity and habitat preferences of orchids in the natural tourist attraction area of R. Soerjo Forest Park (TAHURA) are not yet completely known. Lack of information and the activities of tourist visitors increase the risk of natural orchid habitat degradation. The aim of this research is to determine the diversity and habitat preferences of orchids in R. Soerjo Forest Park. The research design used a line transect method for orchid diversity data and a purposive sampling method with a plot measuring 10 × 10m for habitat preference analysis or environmental data. The research results show that there are 37 species of orchids in the natural tourist attraction area of R. Soerjo Forest Park, which is divided into 25 epiphytic orchids and 12 terrestrial orchids. The results of the Shannon-Wienner analysis show that the orchid diversity index value is 2.46, which is show a medium level of diversity. Dominant orchids grow at an altitude of 1,400–1,600 m.a.s.l. The most dominant orchid species are Nervilia punctata (558), Appendicula angustifolia (296), and A. elegans (130), with an evenness value of 0,32, 0,17, and 0,07. The dominance of N. punctata is influenced by the root shape, which is modified as a tuberous type. The results of redundancy analysis (RDA) show that the environmental variables that most influence the distribution of orchids are air temperature, soil pH levels, light intensity, and elevation.